Urban resilience: Analyzing the policies of U.S. cities. (August 2021) - Woodruff, Sierra; Bowman, Ann O'M.; Hannibal, Bryce; Sansom, Garett; Portney, Kent
Abstract: Resilience has become an important concept in urban governance, yet, the policies that cities actually adopt and implement to build resilience remain largely unknown. The lack of empirical studies on resilience policies hinders our ability to develop theory, ask new questions, and test hypotheses. The goal of this paper is to quantify and compare policies and programs of the 101 largest cities in the U.S. that tangibly affect resilience. We develop a set of resilience policies and then search government websites for evidence of adoption of those policies. To explore patterns of policy adoption, we conduct factor analysis and correlation. We find that resilience does not coalesce around any particular sets of programs. Instead, resilience is a flexible concept, modified to address local context. Substantive groupings of policies do not explain policy adoption. Different dimensions such as funding and level of needed commitment may better explain empirical patterns of policy adoption. Across cities, greater attention must be dedicated to addressing drivers of social vulnerability and climate change impacts. By examining what cities are doing and whether there are underlying patterns to the policies they pursue, we tackle basic empirical questions of how to make sense of the evolving resilience landscape. Highlights: Quantify and compare adoption of resilience policies across 101 largest U.S. cities Large variation in number of policies adopted across cities Across cities, limited action on climate change adaptation, advancing equity, and hardening critical infrastructure Substantive categories of policies do not describe patterns of adoption. Formal resilience programs do not coalesce around a single set of policies.